2013
DOI: 10.1016/j.colsurfa.2013.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen nanobubbles in a water solution of dietary supplement

Abstract: Using gas chromatography, proton nuclear magnetic resonance and qualitative experiments, we demonstrate that a 5 water solution of dissolved dietary supplement, creating negative redox potential, contains invisible hydrogen nanobubbles, which remain in the solution for several hours.Hydrogen, as it was recently revealed by basic and clinical 10 research, is an important physiological regulatory factor producing antioxidant, anti-inflammatory and anti-apoptotic protective effects on cells and organs. 1 Drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Addition of different concentrations of MagH 2 to the yeast-sugar broth (pH 4.4–4.8) caused a significant reduction in the oxidation–reduction potential. Thus, ORP rapidly dropped from +185 mV (regular food) to (–160) – (–166) mV (0.1 mg/ml MagH 2 ), (–320) – (–330) mV (0.3 mg/ml MagH 2 ), and to (–410) – (–470) mV (1 and 3 mg/ml MagH 2 ) and lasted at negative values for at least 4 h. Thus, the observed effects of MagH 2 on fly food were comparable to those observed in water solutions [18], suggesting the existence of molecular hydrogen in the form of nanobubbles and relative stability of its concentrations in the fly food. We also determined that 5 minutes of boiling was sufficient to remove hydrogen gas from solutions, since the ORP values ranged from +180 to +190 mV and were comparable to the ORP values in a regular fly food.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Addition of different concentrations of MagH 2 to the yeast-sugar broth (pH 4.4–4.8) caused a significant reduction in the oxidation–reduction potential. Thus, ORP rapidly dropped from +185 mV (regular food) to (–160) – (–166) mV (0.1 mg/ml MagH 2 ), (–320) – (–330) mV (0.3 mg/ml MagH 2 ), and to (–410) – (–470) mV (1 and 3 mg/ml MagH 2 ) and lasted at negative values for at least 4 h. Thus, the observed effects of MagH 2 on fly food were comparable to those observed in water solutions [18], suggesting the existence of molecular hydrogen in the form of nanobubbles and relative stability of its concentrations in the fly food. We also determined that 5 minutes of boiling was sufficient to remove hydrogen gas from solutions, since the ORP values ranged from +180 to +190 mV and were comparable to the ORP values in a regular fly food.…”
Section: Resultssupporting
confidence: 60%
“…Previous in vitro studies have shown that when dissolved in water, MagH 2 forms H 2 nanobubbles, thereby maintaining high amounts of dissolved H 2 over a relatively long period of time [18]. It also led to a stable negative oxidation-reduction potential at relatively high pH values [18].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly, the HRW is presently mainly obtained by water electrolysis, which requires a hydrogen gas generator. Moreover, the solubility of H 2 in water is very low (approximately 1.84 ml in 100-g H 2 O at 20°C, 1 atm; Safonov and Khitrin, 2013 ), and especially, the residence time of H 2 in HRW is shorter, as the half-time of dissolved H 2 in HRW is less than 1 h ( Figure 2E ), at least under our experimental conditions. The discussed disadvantages may restrict the practical applications of the electrolytic produced HRW.…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, it can remain in higher amounts of dissolved H 2 over a relatively longer period than the electrolytic HRW ( Figure 2E ). It has been reported that hydrolysis of magnesium particles can produce hydrogen nanobubbles that can exist in the water solution of a dietary supplement for a sufficiently long time ( Bunkin et al, 2009 ; Safonov and Khitrin, 2013 ). A balance between surface tension and repulsive forces between surface electric charges is responsible for the stabilization of nanobubbles ( Bunkin et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%